​​Endometriosis Beyond the Body: A Review of Its Impact on Mental Health, Sexual Function, and Fertility - Babiarz, Gabriela; Osiński, Damian; Kawa, Zuzanna; Kasprzak, Maria; Jędrzejewska, Aleksandra; Jureczko, Aleksandra; Kleczaj, Klaudia; Starczewski, Łukasz; Jaworowska, Julia; Kanarszczuk, Julia (Quality in Sport, 2026)
Introduction: Endometriosis is a chronic, hormone-dependent condition affecting up to 15% of women of reproductive age. It is associated with pain, infertility, and a significant reduction in quality of life. Despite increasing awareness, the average diagnostic delay remains between 7 and 11 years. The disease is characterized by chronic pelvic pain, fatigue, dyspareunia, and emotional distress, which may contribute to depression, anxiety, decreased self-esteem, and social isolation. Sexual dysfunction arises from both physical symptoms and psychological factors. Endometriosis is also recognized as a leading cause of infertility. Objective: The aim of this review is to evaluate the impact of endometriosis on women’s mental health, sexual functioning, and fertility, with particular emphasis on diagnostic delays and social stigma. Methods and materials: A literature review was conducted using publications available in the PubMed and Google Scholar databases from 2017-2025. The most relevant and recent studies were selected using appropriate keywords. Conclusions: Endometriosis requires a holistic and multidisciplinary approach that integrates medical management with psychological and sexual health support. Addressing mental health and social well-being is essential for improving overall quality of life in affected women. Early diagnosis and the reduction of stigma remain key challenges in contemporary clinical practice.